Associations between air pollution and pediatric eczema, rhinoconjunctivitis and asthma: A meta-analysis of European birth cohorts. (March 2020) - Fuertes, Elaine; Sunyer, Jordi; Gehring, Ulrike; Porta, Daniela; Forastiere, Francesco; Cesaroni, Giulia; Vrijheid, Martine; Guxens, Mònica; Annesi-Maesano, Isabella; Slama, Rémy; Maier, Dieter; Kogevinas, Manolis; et al.
Highlights: Uncertainty exists as to the role of air pollution on childhood respiratory health. Data from five recent European birth cohorts were meta-analyzed. No evidence found for role of air pollution on asthma and allergies up to 8 years. Findings consistently null across all cohorts considered. Abstract: Background: Uncertainly continues to exist regarding the role of air pollution on pediatric asthma and allergic conditions, especially as air pollution levels have started to decrease in recent decades. Objective: We examined associations of long-term air pollution levels at the home address with pediatric eczema, rhinoconjunctivitis and asthma prevalences in five birth cohorts (BIB, EDEN, GASPII, RHEA and INMA) from seven areas in five European countries. Methods: Current eczema, rhinoconjunctivitis and asthma were assessed in children aged four (N = 6527) and eight years (N = 2489). A multi-morbidity outcome (≥2 conditions versus none) was also defined. Individual outdoor levels of nitrogen dioxide (NO2 ), nitrogen oxides, mass of particulate matter with an aerodynamic diameter <10 μm (PM10 ), 10–2.5 μm (PMcoarse ) and <2.5 μm (PM2.5 ), and PM2.5 absorbance were assigned to the birth, four- and eight-year home addresses using highly defined spatial air pollution exposure models. Cohort-specific cross-sectional associations were assessed using logistic regression models adjusted for demographic and environmental covariates and combined in a random effects meta-analysis. Results: The overall prevalence of pediatric eczema, rhinoconjunctivitis and asthma at four years was 15.4%, 5.9% and 12.4%. We found no increase in the prevalence of these outcomes at four or eight years with increasing air pollution exposure. For example, the meta-analysis adjusted odds ratios (95% confidence intervals) for eczema, rhinoconjunctivitis and asthma at four years were 0.94 (0.81, 1.09), 0.90 (0.75, 1.09), and 0.91 (0.74, 1.11), respectively, per 10 μg/m 3 increase in NO2 at the birth address, and 1.00 (0.81, 1.23), 0.70 (0.49, 1.00) and 0.88 (0.54, 1.45), respectively, per 5 μg/m 3 increase in PM2.5 at the birth address. Discussion: In this large meta-analysis of five birth cohorts, we found no indication of adverse effects of long-term air pollution exposure on the prevalence of current pediatric eczema, rhinoconjunctivitis or asthma.